The Role of Organizational Health in Reducing Manifestations of Organizational Anomie: An Analytical Study of The Opinions of a Sample of Employees at Asiacell Mobile Communications Company/Northern Region - Shareef, Zubaida M.; Abody, Safa’ I. (PROSPECTIVE RESEARCHES, 2026)
This study aims to demonstrate the role of organizational health, with its dimensions (clarity of goals, cohesion, morale, organizational adaptation, and autonomy), in mitigating manifestations of organizational anomie, with its dimensions (organizational non-normativity, lack of organizational values, and organizational cynicism). The study employed a descriptive-analytical approach to present and analyze its findings. Several questions related to the level of organizational health and the prevalence of organizational anomie were discussed, along with identifying the correlation and impact relationships between the two variables. Asiacell Telecommunications Company, with its branches located in northern Iraq, was selected as the study's field of application. The study population comprised employees in the company's branches within the governorates of Erbil, Sulaymaniyah, Duhok, and Nineveh, totaling 1,864 employees. A stratified random sample of 287 individuals was selected. A questionnaire was used as the primary data collection tool, and the data was analyzed using SPSS version 24 and AMOS version 24 through a range of statistical methods. Using frequencies, percentages, arithmetic mean, standard deviation, correlation coefficient, and regression, along with structural equation modeling to analyze direct and indirect influence relationships, the study found significant correlation and influence relationships between organizational health and organizational anumism, indicating that a rise in the level of organizational health effectively contributes to reducing manifestations of organizational anumism. In light of the results, a set of proposals was presented that would support value and behavioral stability within organizations.